Experimental study on the energy dissipation and seismic behavior of RC columns due to repeated earthquakes including vertical excitation - Aydemir, Mueberra Eser; Aydemir, Cem; Arslan, Guray (ELSEVIER SCI LTD, 2023)
The main innovation of this study is to carry out an experimental work focusing on the effects of seismic sequences on RC columns including vertical component of ground motions. The experimental behavior of RC columns under both standard cyclic loading and random earthquake loading is considered. To this purpose, standard cyclic lateral loading history under constant axial loading, standard cyclic lateral loading history under varying axial loading and random lateral and axial loading history to represent random earthquake loading are applied to test columns. Moreover, for random earthquake loading, not only horizontal component of ground motion excitation but also the vertical component is considered. The effect of repeating earthquake excitation on structural response is also investigated through two and three repetitive earthquakes. The effects of six different loading histories on displacement capacity, residual displacement at the end of test, maximum residual displacement measured during test, damage states and dissipated energy capacities are examined comparatively in the test program. It is found that, loading history especially variability in axial loading, plays a very important role on the response of columns.
Keywords: Earthquake engineering; RC Columns; Repeated earthquakes; Vertical component of ground motion; MOMENT-RESISTING FRAMES; DUCTILITY DEMANDS; MULTIPLE; Engineering